1165 Rectal Swabs: an Increasingly Important Component of Nicu Infection Surveillance Programmes?. (October 2012) - Suviste, J; Gray, J; Morgan, I; Patel, M
Abstract : Background and Aims: Gram-negative bacteria present an increasing threat to NICU babies. Because the gastrointestinal tract is the primary colonisation site, we added rectal swabbing to routine admission and weekly screening of babies from September 2010. We consider here the impact of this strategy on clinical and infection control management. Methods: Rectal swabs were cultured for the following Gram-negative bacteria of interest (GNBi): Serratia; gentamicin-resistant &/or ESBL-producing Enterobacteriaceae; Pseudomonas aerugionsa (PA). Colonised babies were isolated, but were not treated with antibiotics unless clinically indicated. Results: GNBi (except PA) were isolated from 55 (2.6%) of 2101 admissions, September 2010–March 2012: 21 gentamicin-resistant Enterobacteriaceae; 9 ESBL-producing Enterobacteriaceae; 25 Serratia. 45 of the GNBi were detected in rectal swabs: in 38 (64.7%) rectal swabs were the first, and in 28 (33.3%) the only, culture-positive samples. Only one baby had GNBi infection (bacteraemia on the same day as a positive rectal swab). There were 13 instances of 2–3 babies having the same bacterium within 7 days of each other. In one case, seven babies were found with Serratia over 7 days. PA results are not shown for the first 7 months, because of an exceptional event causing PA colonisation then. After April 2011 there were 5 cases (4 detected on rectal swabs: the only positive site in 3): there was no clustering of these cases. Conclusion: An unexpectedly high proportion of NICU babies had GNBi. The high frequency of patient-to-patient transmission suggests that rectal screening can be an important tool in controlling these bacteria.